Patient-reported satisfaction and study drug discontinuation: post-hoc analysis of findings from ROCKET AF - Ungar, Leo; Rodriguez, Fatima; Hellkamp, Anne S.; Becker, Richard C.; Berkowitz, Scott D.; Breithardt, Guenter; Fox, Keith A. A.; Hacke, Werner; Halperin, Jonathan L.; Hankey, Graeme J.; Nessel, Christopher C.; Singer, Daniel E.; et al. (Cardiology and therapy, 2019)
Introduction: Patient-reported outcomes (PROs) and satisfaction endpoints are increasingly important in clinical trials and may be associated with treatment adherence. In this post hoc substudy from ROCKET AF, we examined whether patient-reported satisfaction was associated with study drug discontinuation. Methods: ROCKET AF (n = 14,264) compared rivaroxaban with warfarin for prevention of stroke and systemic embolism in patients with atrial fibrillation. We analyzed treatment satisfaction scores: the Anti-Clot Treatment Scale (ACTS) and Treatment Satisfaction Questionnaire for Medication version II (TSQM II). We compared satisfaction with study drug between the two treatment arms, and examined the association between satisfaction and patient-driven study drug discontinuation (stopping study drug due to withdrawal of consent, noncompliance, or loss to follow-up). Results: A total of 1577 (11%) patients participated in the Patient Satisfaction substudy; 1181 (8.3%) completed both the ACTS and TSQM II 4 weeks after starting study drug. Patients receiving rivaroxaban did not experience significant differences in satisfaction compared with those receiving warfarin. During a median follow-up of 1.6 years, 448 premature study drug discontinuations occurred (213 rivaroxaban group; 235 warfarin group), of which 116 (26%) were patient-driven (52 [24%] rivaroxaban group; 64 [27%] warfarin group). No significant differences were observed between satisfaction level and rates of patient-driven study drug discontinuation. Conclusions: Study drug satisfaction did not predict rate of study drug discontinuation. No significant difference was observed between satisfaction with warfarin and rivaroxaban, as expected given the double-blind trial design. Although these results are negative, the importance of PRO data will only increase, and these analyses may inform future studies that explore the relationship between drug-satisfaction PROs, adherence, and clinical outcomes. ClinicalTrials.gov - NCT00403767. Funding: The ROCKET AF trial was funded by Johnson & Johnson and Bayer. Electronic supplementary material - The online version of this article (10.1007/s40119-019-00146-6) contains supplementary material, which is available to authorized users.
Gesehen am 23.04.2020